Hydroboration of Alkyne‐Functionalized 1, 3, 2‐Benzodiazaboroles. Issue 14 (20th March 2013) - Weber, Lothar; Eickhoff, Daniel; Halama, Johannes; Werner, Stefanie; Kahlert, Jan; Stammler, Hans‐Georg; Neumann, Beate
Abstract: Reactions of equimolar amounts of dicyclohexylborane (DCB) with a series of 2‐alkynyl‐1, 3‐diethyl‐1, 3, 2‐benzodiazaboroles R–C≡C–B(NEt)2 C6 H4 (1 : R = n Bu, 2 : R = t Bu, 3 : R = Ph, 4 : R = p ‐Me2 NC6 H4, 5 : R = p ‐MeOC6 H4 ) regioselectively afforded the 1, 1‐diborylalkenes ( Z )‐R(H)C=C{(B{NEt}2 C6 H4 )B( c ‐C6 H11 )2 } (7a –11a ) as the result of a cis ‐addition of the BH bond of the borane to the C≡C triple bond in compounds1 to5 . In contrast to this, reaction of Me3 Si–C≡C–B(NEt)2 C6 H4 (6 ) with HB( c ‐C6 H11 )2 yielded a 2.5:1 mixture of the 1, 2‐diborylated alkene ( Z )‐Me3 Si{( c ‐C6 H11 )2 B}C=CHB(NEt)2 C6 H4 (12b ) and the 1, 1‐regioisomer ( Z )‐Me3 Si(H)C=C{B(NEt)2 C6 H4 }{B( c ‐C6 H11 )2 } (12a ). These results were rationalized by the differing π‐acceptor qualities of the benzodiazaborolyl and trimethylsilyl substituents at the C≡C triple bond in compounds1 to6 . The novel products7 –12 were characterized by elemental analysis, mass spectrometry and NMR spectroscopy ( 1 H, 11 B, and 13 C NMR). The molecular structures of9b and12b were substantiated by single‐crystal X‐ray diffraction analysis. Abstract : The hydroboration of the C≡C bond of a series of 2‐alkynyl‐1, 3‐diethyl‐1, 3, 2‐benzodiazaboroles R‐C≡C‐B(NEt)2 C6 H4 (R = n Bu, t Bu, Ph, p Me2 NC6 H4, p MeOC6 H4 ) with dicyclohexylborane regioselectively afforded 1, 1‐diborylalkenes ( Z )‐R(H)C=C‐{(B{NEt}2 C6 H4 )BCy2 }. Reaction of the trimethylsilyl‐ethynyl derivative with HBCy2 yielded a 2.5:1 mixture of the 1, 2‐ and 1, 1‐diborylated 2‐alkenyl‐benzodiazaboroles.